Strain Rate Contribution due to Dynamic Recovery of Ultrafine-Grained Cu-Zr as Evidenced by Load Reductions during Quasi-Stationary Deformation at 0.5 T-m - Blum, Wolfgang; Dvorak, Jiri; Kral, Petr; Eisenlohr, Philip; Sklencka, Vaclav (Metals, 2019)
During quasi-stationary tensile deformation of ultrafine-grained Cu-0.2 mass%Zr at 673 K and a deformation rate of about 10(-4) s(-1) load changes were performed. Reductions of relative load by more than about 25% initiate anelastic back flow. Subsequently, the creep rate turns positive again and goes through a relative maximum. This is interpreted by a strain rate component E- associated with dynamic recovery of dislocations. Back extrapolation indicates that E- contributes the same fraction of (20 +/- 10)% to the quasi-stationary strain rate that has been reported for coarse-grained materials with high fraction of low-angle boundaries; this suggests that dynamic recovery of dislocations is generally mediated by boundaries. The influence of anelastic back flow on E- is discussed. Comparison of E- to the quasi-stationary rate points to enhancement of dynamic recovery by internal stresses. Subtraction of
CRIS-Team WoS Importer:2020-01-10